Anti-inflammatory effects of interleukin-35 in acquired aplastic anemia. Issue 2 (December 2015) - Yu, Wei; Ge, Meili; Lu, Shihong; Shi, Jun; Li, Xingxin; Zhang, Jizhou; Wang, Min; Huang, Jinbo; Shao, Yingqi; Huang, Zhendong; Zhang, Jing; Nie, Neng; et al.
Highlights: Plasma IL-35 levels were decreased in AA patients compared to healthy controls. Decreased IL-35 was closely correlated with disease severity of AA. IL-35 modulated the secretion of pro- and anti-inflammatory cytokines of AA. IL-35 regulated the differentiation of T cell subsets of AA. Abstract: Interleukin (IL)-35 is a novel regulatory cytokine primarily produced by regulatory T cells. Accumulating evidence has established that IL-35 plays an important role in the regulation of immune homeostasis, but little is known regarding the function of IL-35 in acquired aplastic anemia (AA). The aim of the present study was to investigate the expression of IL-35 and its effects on T cell response in AA. Our study demonstrated that significantly decreased plasma levels of IL-35 in AA were closely correlated with disease severity. In vitro stimulation experiment further confirmed the anti-inflammatory effects of IL-35, including suppressing the proliferation of CD4 + and CD8 + effector T cells, inhibiting the secretion of interferon-γ, tumor necrosis factor-α and IL-17 and promoting the production of transforming growth factor-β by peripheral blood mononuclear cells from patients with AA. Furthermore, we established that IL-35 inhibited the differentiation of type 1 T cells and T helper 17 cells but promoted the differentiation of type 2 T cells. Accordingly, the expression of T-bet and RORγt was inhibited while the expression of GATA3 was induced after IL-35 treatment. In summary, our findings suggested that decreased IL-35 might contribute to the loss of immune-tolerance and be critically involved in the pathogenesis of AA.